PENGARUH SELF ASSESSMENT SYSTEM TERHADAP KEPATUHAN WAJIB PAJAK DI BONE BOLANGO - Salsa Nelisa; Hartati Tuli; Siti Pratiwi Husain (Universitas Negeri Gorontalo, 2026)
This study aims to determine the effect of the implementation of the Self Assessment System on the compliance of Individual Taxpayers (WPOP) with fixed income (private employees) in Bone Bolango Regency. The method used in this research is a quantitative approach with primary data sources obtained through distributing questionnaires to respondents. The sampling technique used convenience sampling, with respondents being private employee WPOP in Bone Bolango Regency. The data analysis techniques used were descriptive analysis and logistic regression to statistically test the effect of the independent variable on the dependent variable. The results of this study indicate that the implementation of the Self Assessment System has a significant negative effect on the compliance of Individual Taxpayers (WPOP) with fixed income (private employees) in Bone Bolango Regency. This is evidenced by the logistic regression analysis results with a significance value of 0.039 ( 0.05), a coefficient value of -0.302, and an Odds Ratio (Exp(B)) value of 0.740, which means that an increase in the implementation of the Self Assessment System actually reduces the chance of compliance of Individual Taxpayers (WPOP) private employees in Bone Bolango Regency.